The apostle [large type] : a thriller - Thor, Brad (Thor, Brad. Scot Harvath., 2009)
When American doctor Julia Gallo is kidnapped in Afghanistan, the terms of her ransom leave the president with only one course of action: send covert counterterrorism operative Scot Harvath to free the man the kidnappers demand as ransom--al-Qaeda mastermind, Mustafa Khan.